Jogo digital para reconhecimento de palavras: análise comparativa entre as versões com instruções implícitas e explícitas - Anderson Pimentel Borges (2013)
The objective of this research was to verify the influence of the instruction type - implicit or explicit - in the Pac-Mouse game repeatability and also in children performance, in literacy phase, to recognize the syllables that form words. For that, the Pac-Mouse was developed in two versions: explicit and implicit. The explicit version contained information which guided the player on the necessary procedures to form the words. Already the game with implicit instructions did not present any orientation on the order that the syllables should be taken. To test the cause and effect relation between the implicit and explicit instructions and the game repeatability and also the player performance, 20 public school children from Contagem were selected to live the presyllabic phase, in agreement with Ehri (2002) and Ferreiro (1985). They were divided in two groups of ten children, ranging from 5 to 6 years old, and each one of them played a version of the game. The implicit version obtained more repeatability and helped the player enhance his performance in the game either for those whom had more difficulty to win the challenges and the objectives or those whom succeeded in all the phases. The larger game time gave each child more possibilities to learn with the errors committed in relation to the cooks escape, movement in the game kitchen, use of cheese power and words forming process. On the words recognition and the writing development, after the end of the Pac-mouse session, five children, in a total of twenty, got to write the words seen in the game as if they were in the syllabic-alphabetical phase. The results of the research with the Pac-mouse implicit and explicit version contributed to notice that the game development demands special care in every single detail, even a color change shall generate impacts of great relevance for the product educational content acceptance and assimilation before the target public.